A study of emission of nanoparticles during physical processing of aged polymer-matrix nanocomposites - Gendre, Laura (Cranfield University, 2016)
Nanotechnology research and its commercial applications have experienced an exponential rise in the recent decades. Although there are a lot of studies with regards to toxicity of nanoparticles, the exposure to nanoparticles, both in terms of quality and quantity, during the life cycle of nanocomposites is very much an unknown quantity and an active area of research. Unsurprisingly, the regulations governing the use and disposal of nanomaterials during its life cycle are behind the curve. This work aims to assess the quantity of nanoparticles released along the life cycle of nanocomposites. Machining operations such as milling and drilling were chosen to simulate the manufacturing of nanocomposites parts, and impact testing to recreate the end-of-life of the materials. Several studies have tried to simulate different release scenarios, however these experiments had many variables and in general were not done in controlled environments. In this study, a reliable method was developed to assess the release of nanoparticles during machining and low velocity impact of nanocomposites. The development and validation of a new prototype used for measurement and monitoring of nanoparticles in a controlled environment is presented, as along with release experiments on different nanocomposites. Every sample tested was found to release nanoparticles irrespective of the mechanical process used or the type of material tested. Even neat polymers released nanoparticles when subjected to mechanical forces. The type of matrix was identified to play a major role on the quantity of nanoparticles release during different process. Thermoset polymers (and especially polyester) were found to release a higher number concentration of particles, mainly due to their brittle properties. A polyester sample was found to release up to 48 times more particles than a polypropylene one during drilling. The nanofiller type and percentage used to reinforce the polymer is also a key point. For example, the addition of 2 wt.% of nano-alumina into polyester increases the number concentration of particles by 106 % following an impact. The nanofiller chosen and its quantity affect the mechanical properties and machinability of the composites and therefore its nanoparticles release potential. The mechanical process and the process parameters chosen were also found to be crucial with regards to the nanoparticles released with different trends observed during drilling and impact of similar materials. Finally, thermal ageing of nanocomposites increases the number concentration of nanoparticles released (by 8 to 17 times after 6 weeks).
Keywords: Nanosafety; Nanocomposites machining; Low Velocity Impact; Life Cycle Analysis; Standardization